Upaya Meningkatkan Hasil Belajar Peserta Didik pada Muatan Matematika Melalui Model Discovery Learning di Kelas V SDN 146/X Tanjung Solok pada Semester Ganjil Tahun Ajaran 2021/2022 - Sahriani Sahriani (Departement of Mathematics Education, 2022)
The problem in this research is that the learning outcomes of students' mathematics content are still low and there is a need for an action to improve it. The purpose of this study was to obtain information and discuss efforts to improve student learning outcomes on mathematics content through discovery learning models in class V SDN 146/X Tanjung Solok in the odd semester of the 2021/2022 academic year. This research is a classroom action research by following four stages, namely planning, implementation, observation, and reflection. The research location is at SDN 146/X Tanjung Solok in the odd semester of the 2021/2022 academic year with the research subjects being 21st grade students of SDN 146/X Tanjung Solok. Data collection techniques using tests, field notes, interviews and documentation. Data were analyzed using percentages and data reduction. Based on the results of the research and discussion, it can be concluded that through discovery learning learning models can improve the learning outcomes of the fifth grade students of SDN 146/X Tanjung Solok, which is characterized by an increase in the average learning outcome and the percentage of completeness of each cycle with the act of giving rewards.